Monitoring of concrete structure damage caused by sulfate attack with the use of embedded piezoelectric transducers. (10th September 2019) - Zou, Dujian; Cheng, Hanbin; Liu, Tiejun; Qin, Shanshan; Yi, Ting-Hua
Abstract: Sulfate attack is a major threat to the durability of concrete structures and causes surface scaling, expansive disruption, and loss of cohesion of cement hydration products. Properties such as expansion strain or the mass loss ratio of the concrete specimens are commonly used in lab testing to identify the deterioration of concrete under sulfate attack. However, these indicators and testing methods are rarely used for the in situ monitoring of concrete structures in aggressive sulfate environments since sulfate attack typically occurs either underground or below the water level. In this study, an active sensing method is proposed to monitor the deterioration of concrete exposed to a sulfate attack. Three concrete specimens with embedded smart aggregates were fabricated to measure the wave velocity at different concrete depth ranges and sulfate attack times, and 48 cubic specimens were cast to measure the compressive strength development of concrete in water or an 8% sulfate sodium solution. The test results showed that the measured wave velocity was sensitive to the deterioration level of concrete. This indicates that the sulfate attack level can be evaluated with respect to the concrete depth using the proposed monitoring method. A preliminary relationship between the measured wave velocity and deteriorated strength of concrete specimen was established. This study provides a valuable insight into the use of in situ health monitoring and a useful strength prediction method for concrete structures experiencing a sulfate attack.